Self-organization of a wheeled robotic swarm using virtual spring-damper mesh - Wiech, Jakub (Institute of Advanced Engineering and Science, 2023)
The article analyzes the problem of self-organization of randomly placed wheeled robots around a stationary reference point, into a given shape of a regular polygon. The paper gives an answer to the question how virtual forces from virtual spring-damper connections between robots allow self-organization of the swarm into the desired shape. The presented method of control is described in detail with the description of i-th robot dynamics and tested numerically and experimentally. The swarm's self-organization is aimed at moving randomly spaced robots with a random frame orientation to a given distance to a reference point, reaching and maintaining a given distance between neighboring robots. The paper presents the results of numerical tests and experimental research and ends with discussion and conclusions. The paper's results could be expanded for applications related to spacial distribution of mobile robots.